2009
DOI: 10.1016/j.febslet.2009.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic functional effects of the first epilepsy‐associated mutation in the human CHRNA2 gene

Abstract: Autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) can be caused by mutations in the neuronal nicotinic acetylcholine receptor (nAChR) subunit genes CHRNA4 and CHRNB2. Recently, a point mutation (alpha2-I279N) associated with sleep-related epilepsy has been described in a third nAChR gene, CHRNA2. We demonstrate here that alpha2-I279N can be co-expressed with the major structural subunit CHRNB2. alpha2-I279N causes a marked gain-of-function effect and displays a distinct biopharmacological profile, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Epilepsy occurs in 5-49% of people with autism (Levy et al, 2009). Genetic abnormalities in CHRN4A and CHRNB2, encoding the  and  nAChR subunits respectively, are sufficient to cause autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) (De Fusco, 2000;Bertrand, 2002;Steinlein, 2002;Hoda, 2009) (Ross et al, 2000) and the 2 nAChR knockout animal shows abnormal sleep pattern (Lena et al, 2004). These studies demonstrate that behaviors regulated by nAChRs are disparate and commonly aberrant in ASD and suggest the potential for nAChR-acting drugs in the treatment of ASD.…”
Section: Nachrs Modulate Multiple Behaviors Deficient In Asdmentioning
confidence: 99%
“…Epilepsy occurs in 5-49% of people with autism (Levy et al, 2009). Genetic abnormalities in CHRN4A and CHRNB2, encoding the  and  nAChR subunits respectively, are sufficient to cause autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) (De Fusco, 2000;Bertrand, 2002;Steinlein, 2002;Hoda, 2009) (Ross et al, 2000) and the 2 nAChR knockout animal shows abnormal sleep pattern (Lena et al, 2004). These studies demonstrate that behaviors regulated by nAChRs are disparate and commonly aberrant in ASD and suggest the potential for nAChR-acting drugs in the treatment of ASD.…”
Section: Nachrs Modulate Multiple Behaviors Deficient In Asdmentioning
confidence: 99%
“…In this initial study, however, functional nAChRs were obtained only by expression of the α2 subunit with the β4 subunit and therefore differed from the native receptors that most likely mainly result from the assembly of α2 with β2. Further studies carried out with the I279N α2 mutant expressed with the control β2 confirmed the gain of acetylcholine sensitivity caused by this mutation together with additional modifications in the receptor properties such as a gain of sensitivity to nicotine and in the carbamazepine blockade [29].…”
Section: Physiological Properties Of Mutated Channelsmentioning
confidence: 97%
“…Derzeit sind 4 Mutationen im CHRNA4-und 3 im CHRNB2-Gen (β 2 -Untereinheit) sowie eine weitere Mutation in der α 2 -Untereinheit (CHRNA2; [13,29,30]) beschrieben; hierbei sind die meisten in den porenformenden, transmembranä-ren M2-Segmenten lokalisiert. Hinsichtlich des Pathomechanismus wird eine erhöhte Acetylcholinsensitivität, also ein Funktionsgewinn, angenommen [13,31]. Thalamokortikale Schleifen haben für die rhythmische Aktivität während des Schlafs eine wichtige Bedeutung, insbesondere für Projektionen in den Frontallappen, an denen auch cholinerge Neurone beteiligt sind.…”
Section: Autosomal-dominante Nächtliche Frontallappenepilepsieunclassified